The Lipid Droplet as a Potential Therapeutic Target in NAFLD - Goh, Vera J.; Silver, David L. (Seminars in Liver Disease, 2013)
Nonalcoholic fatty liver disease (NAFLD) is a growing problem worldwide. Nonalcoholic fatty liver disease is characterized by an abnormal accumulation of triglyceride-rich lipid droplets (LDs) in the liver, which can lead to liver inflammation and metabolic disturbances. Lipid droplets are dynamic organelles that have recently gained considerable scientific interest. Their formation and growth are regulated processes requiring the participation of many endoplasmic reticulum- (ER-) and LD-associated proteins, which may serve as potential therapeutic targets for NAFLD. Protein families such as fat-inducing transmembrane proteins 1 and 2 (FITM1/FIT1 and FITM2/FIT2), the CIDE family of proteins, and the perilipin family, play important roles in LD biology. In this review, the authors discuss current views on LD formation and growth, and how various proteins may affect LD metabolism and lipoprotein assembly in the pathogenesis of NAFLD.
Keywords: nonalcoholic fatty liver disease; lipid droplets; triglyceride